The Effect Digital Creative Economy Sector to Economic Growth in Bangka Belitung : Theory Perspective - Yuristian Eka Prakarsa; Nizwan Zukhri; Ari Agung Nugroho (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
This study aims to investigate the relationship between the effect digital creative economy sector to economic growth in Bangka Belitung. In the context of an ever-changing global economy, the digital and creative economy sector has emerged as one of the significant growth engines. This research uses a secondary data analysis method involving economic, digital, economic growth, employment, and creative economy sector data. The study identifies digital creative economy in sub sectors that have greater growth potential than others. This sector-specific analysis provides deeper insights into how different segments of the creative economy can more effectively contribute to the economic development in Bangka Belitung. The creative economy has become a recognized driver of economic development in recent years.The implication of these findings is the need to develop more robust and targeted policy strategies to support the growth digitalization of the creative economy sector. The effect digital creative economy growth are access to information and markets, access to financial services, Marketing and Market Expansion, Skills and Productivity Improvement. Keywords : economic growth, digital, creative economy